Seismic mapping and geomechanical analyses of faults within deep hot granites, a workflow for enhanced geothermal system projects. (January 2015) - Abul Khair, H.; Cooke, D.; Hand, M.
Highlights: We used 3D seismic to image the granitic bodies and to build a structural model for unconventional geothermal projects. We used resistivity logs and formation tests to estimate the stress tensor within the basin. We conducted fault geomechanical fluid susceptibility analysis by modelling stress tensor on the structural model. The research took the Cooper Basin as an example to generate a workflow for EGS. A workflow was generated for locating potential spots for enhanced geothermal systems. Abstract: Areas with deep seated radioactive granites are considered targets for enhanced geothermal system (EGS) projects. These areas normally exhibit high heat flow and temperature anomalies related to granitic bodies. High concentrations of uranium within the granites are the most likely cause of the anomalous temperatures. Elevated temperatures are also resulted to high heat flow and thick sedimentary rock cover that includes insulating materials such as coals and gas reservoirs. In this study we investigated the use of 3D seismic amplitudes and attributes to map deep granitic bodies and faults in the Cooper Basin of South Central Australia. We established a workflow for possible geomechanical fluid flow susceptibility analyses for faults that intersect granites. The far field stress tensor must be interpreted through analyses of image logs and formation tests. Our geomechanical analyses models show how this stress tensor affects basement faults interpreted from 3D seismic surveys. Normal stresses, shear stresses, slip tendency, and distance to failure should be modelled for the faults that cut the granites. The optimal orientation of faults that can be possible conduits are then located. We suggest that the optimal injection and production wells should be located at tips of shallow faults that penetrate the granites. We anticipate that short horizontal faults that are located far from other faults will form a more secure fluid conduit. Finally, this study can be a workflow to evaluate the relative merit of future enhanced geothermal system projects.